2019
DOI: 10.1155/2019/3546153
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature and Accelerator on Gel Time and Compressive Strength of Resin Anchoring Agent

Abstract: In this study, we examined the effects of different temperatures and accelerators on the gelation (gel) time and compressive strength of a Polyethylene Terephthalate (PET)-type unsaturated polyester resin anchorage agent. First, the formation temperature of 20–70°C was simulated using self-made test equipment. N,N-Dimethylaniline (DMA), N,N-dimethylp-toluidine (DMT), and hydroquinone were selected as accelerators to determine gel time and heat release peak. The gel time of an anchorage agent is strongly influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…DMT was more active and hence more suitable for low-temperature environment than DMA. 26 Here, we added DMT as a new polymerization accelerator for embedding at −20°C. After extensive testing, we found that 0.6% BPO and 0.7% DMT were the optimal concentration combination.…”
Section: Discussionmentioning
confidence: 99%
“…DMT was more active and hence more suitable for low-temperature environment than DMA. 26 Here, we added DMT as a new polymerization accelerator for embedding at −20°C. After extensive testing, we found that 0.6% BPO and 0.7% DMT were the optimal concentration combination.…”
Section: Discussionmentioning
confidence: 99%
“…e curing dosage of the anchoring agent is 4% of the mass of the resin mortar, the curing time is 180 s, the strength of the anchoring agent is 65 MPa, the elastic modulus is 10.5 GPa, and Poisson's ratio is 0.26. In addition, the compressive strength of the anchoring agent at different temperatures is shown in Table 2 [20,21].…”
Section: Anchoring Agentmentioning
confidence: 99%